Manipulation of Light Signal Transduction Factors as a Means of Modifying Steroidal Glycoalkaloids Accumulation in Tomato Leaves - Wang, Cui-cui; Meng, Lan-huan; Gao, Ying; Grierson, Donald; Fu, Da-qi (Frontiers in Plant Science, 2018)
Steroidal glycoalkaloids (SGAs) are cholesterol-derived specialized metabolites produced by Solanaceous plant species. They contribute to pathogen defense but are considered as anti-nutritional compounds and toxic to humans. Although the genes involved in the SGA biosynthetic pathway have been successfully cloned and identified, transcription factors regulating this pathway are still poorly understood. We report that silencing tomato light signal transduction transcription factors ELONGATED HYPOCOTYL 5 (SlHY5) and PHYTOCHROME INTERACTING FACTOR3 (SlPIF3), by virus-induced gene silencing (VIGS), altered glycoalkaloids levels in tomato leaves compared to control plant. Electrophoretic mobility shift assay (EMSA) and Chromatin immunoprecipitation (ChIP) analysis confirmed that SlHY5 and SlPIF3 bind to the promoter of target genes of GLYCOALKALOID METABOLISM (GAME1, GAME4, GAME17), affecting the steady-state concentrations of transcripts coding for SGA pathway enzymes. The results indicate that light-signaling transcription factors HY5 and PIF3 regulate the abundance of SGAs by modulating the transcript levels of these GAME genes. This insight into the regulation of SGA biosynthesis can be used for manipulating the level of these metabolites in crops.